Muyûl al-Talâmidh fî Tadrîs al-Qirâ’ah - Ritonga, Mahyudin; Sartika, Fitria (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2021)
Purpose- This study aims to reveal the spirit and motivation of learners in studying Qiro'ah, specifically the study is focused on the description of the forms of motivation of learners, factors that affect the motivation of learners in learning qiro'ah, as well as the steps taken by teachers in improving the spirit of learners in learning qiro'ah. Design/Methodology/Approach- Research is carried out with a qualitative approach, data collection techniques are observation, interview and documentation studies. This approach was chosen considering that the research data found and analyzed is natural without treatment. Findings: The results of the study are first, the spirit of learners in learning qiro'ah is very low, this is evidenced by the tasks given by Arabic teachers are not completed thoroughly by many students. Second, low motivation is influenced by internal and external factors, ineternal factors include weak ability to apply qawa'id al-lughah in reading Arabic scripts, knowledge that is less related to the urgency of reading ability, while external factors include less support from more able friends, improper media selection, methods used by teachers sometimes out of sync with learners. Third, teachers make efforts to increase reading motivation by providing reinforcement for learners related to the importance of reading skills, finding and using the right qiro'ah learning media, updating qiro'ah learning methods, increasing supervision of established tasks. Research Limitation/Implications-Researchers have not revealed anything related to the ability to read Arabic, therefore researchers and observers of Arabic learning can continue research on various aspects relevant to this study, such as studying the correlation of motivation to study qiro'ah with understanding of Arabic reading manuscripts.